Implementasi Kaidah Fiqhiyyah Kulliyah dalam Penyelesaian Masalah Hukum Ekonomi Syariah di Era Digital - Ahmad Al Fauzan; Danar Moreno; Gilang Ramadhan; Abdul Rahman Sofyan (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The rapid shift toward digitalization has introduced new financial products and transactional models that require a more adaptive and integrated approach to Islamic legal reasoning. This study analyzes the role of al qawāid al fiqhiyyah al kulliyyah in addressing contemporary legal challenges within the digital economy and develops a methodological framework for assessing the Sharia compliance of emerging digital practices. Using a qualitative library based method, the research engages classical and modern legal sources by combining substantive contract analysis, application of core legal maxims, and maqāṣid al sharīʿah evaluation. Several case domains are examined, including e commerce arrangements, Islamic P2P financing structures, cryptocurrency usage, and blockchain based smart contracts, to identify potential issues related to gharar, ḍarar, and misalignment with Sharia objectives. The findings show that the five universal legal maxims offer a strong and adaptable foundation for managing uncertainty, promoting transactional fairness, and safeguarding consumer interests in digital environments. The study also proposes a five stage methodological model designed to guide Sharia supervisory boards, regulators, and industry practitioners in developing policies, operational standards, and compliance mechanisms suited to Islamic digital financial services.